Antimicrobial drug use and the risk of glioma: A case–control study. (6th September 2022) - Haedenkamp, Tareq M.; Leitzmann, Michael F.; Linker, Ralf A.; Meier, Christoph; Becker, Claudia; Jick, Susan; Hau, Peter; Seliger, Corinna
Abstract: Background: The use of antibiotics has been associated with increased risks of various cancers. Comprehensive information on the association of antibiotic use with the risk of glioma is lacking. Methods: We performed a large case–control study based on the Clinical Practice Research Datalink (CPRD) GOLD from the United Kingdom. We identified 4423 glioma cases recorded between 1995 and 2020 and matched them to controls (1:10) on the date of diagnosis (i.e., the index date), age, sex, general practice, and number of years of medical history in the database prior to the index date. We conducted conditional logistic regression analyses to calculate odds ratios (ORs) with 95% confidence intervals (CIs). The exposures of interest were the use of antimicrobial drugs, including antibacterial, antiviral, antifungal, antiprotozoal, and anthelmintic drugs with specific subclasses, where possible. Results: We found no substantially increased risk of glioma after ever‐use of antibiotics (OR 1.13, 95% CI 1.03–1.24). The risk did not increase with the increasing number of prescriptions received or with increasing time from first use to cancer diagnosis. The use of polyenes was associated with a weakly decreased risk of glioma (OR 0.81, 95% CI 0.67–0.96). Abstract : In this large case–control study, we found no substantially increased risk of glioma among users of most antimicrobial drugs. The risk did not increase with increasing numbers of prescriptions received or with increasing time from first use to cancer diagnosis. The use of polyenes yielded a weak inverse association with the risk of glioma, which needs to be confirmed independently.